2013
DOI: 10.1186/2193-1801-2-277
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of strategies to prevent weight gain among women with and at risk for breast cancer: a systematic review

Abstract: BackgroundObesity affects cancer risk and treatment outcomes. Preventing weight gain may prevent some cancers, improve cancer outcomes, reduce cancer recurrence and increase cancer-related survival. We performed a systematic review to identify strategies to prevent weight gain in individuals with or at risk for breast cancer.FindingsWe included 2 studies from 27,879 citations. In premenopausal women at risk for breast cancer, a low fat diet prevented weight gain at 12 months. Among women with breast cancer, ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…A systematic review showed that there are some stratAragón F et al . Diet and breast cancer egies to prevent weight gain that may decrease the risk of breast cancer or improve cancer outcomes in women with breast cancer [31] . de Lorgeril and Salen suggested that a high omega-3 to omega-6 ratio, such as the case of traditional Mediterranean diet, reduce the risk of cancer, especially breast cancer [32] .…”
Section: Nutrtion and Breast Cancermentioning
confidence: 99%
“…A systematic review showed that there are some stratAragón F et al . Diet and breast cancer egies to prevent weight gain that may decrease the risk of breast cancer or improve cancer outcomes in women with breast cancer [31] . de Lorgeril and Salen suggested that a high omega-3 to omega-6 ratio, such as the case of traditional Mediterranean diet, reduce the risk of cancer, especially breast cancer [32] .…”
Section: Nutrtion and Breast Cancermentioning
confidence: 99%
“…Breast cancer is the second most common cancer amongst women worldwide (Chlebowski et al, 2008;Ferlay et al, 2010), with nearly 1.7 million new cases diagnosed in 2012, that comprising about 12% of all new cancer cases and 25% of all cancers in women (Hussain M et al, 2014). Breast cancer being one of the leading cancers among women in developing countries (Rao et al, 2005), that comprised the 21.4% of female cancers in Iran (Babu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in maintaining weight loss long-term has been heavily attributed to the failure in maintaining changes to physical activity and diet . Given maintenance of physical activity and dietary behaviour change is required for weight loss maintenance and for long-term health benefits, the difficulty in maintaining these behaviour changes long-term is concerning and problematic (Chaudhry et al, 2013;. There is a clear gap in the evidence and subsequent need to direct attention to understanding the interventions that promote maintenance of behaviour change (Akers et al, 2010;Fjeldsoe et al, 2012;Gourlan et al, 2011;).…”
Section: Patterns Of Physical Activity and Dietary Behaviour Change Mmentioning
confidence: 99%
“…There have been numerous calls in the literature to better understand how to promote maintenance of behaviour change in order to inform evidence-based practice that will lead to sustained health benefits (Chaudhry et al, 2013;Crain et al, 2010;Lawler et al, 2014;. Maintenance of behaviour change is particularly important for cancer survivors, as they are at an increased risk (compared to those without cancer) for cancer recurrence and mortality, weight gain, as well as a range of lifestyle-related chronic conditions (Ballard-Barbash et al, 2012;Ewertz et al, 2011;Griffiths et al, 2014;Land et al, 2012).…”
Section: Significance Of This Researchmentioning
confidence: 99%
See 1 more Smart Citation